Analisis Perbedaan Kinerja Perusahaan antara Perusahaan yang Terindeks LQ45 dengan Perusahaan Non LQ45 - Gandawati, Ida Ayu Nyoman Utari; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
This study aims to determine and obtain empirical evidence about the difference performance of companies in LQ45 indexed companies and non-LQ45 companies. This research was conducted at non-financial companies on LQ45 indexed companies and non-LQ45 companies listed on the Indonesia Stock Exchange in 2016-2018. The sample of this study is chosen using purposive sampling technique and 45 non-financial companies were obtained for each LQ45 and non-LQ45 indexed group of companies, so the number of observations in this study was 270 observations. The data analysis technique used is the Mann-Whitney U Test. The results showed that the LQ45 indexed group of companies had a higher average liquidity and profitability compared to non-LQ45 companies, while in terms of average the leverage value of LQ45 companies was lower compared to non-LQ45 companies. Keywords: Company Performance; LQ45; Non LQ45.